Redescription of Ateleopus indicus Alcock 1891, (Teleostei: Ateleopodiformes: Ateleopodidae), and its reassignment to the genus Parateleopus - Kaga, Tatsuya; Iwamoto, Tomio; Mishra, Subhrendu Sekhar (Zootaxa, 2022)
The Indian jellynose fish Ateleopus indicus Alcock 1891 is redescribed as a member of the genus Parateleopus based on examination of the holotype and 11 other specimens. The character states of small mouth, no sharp spine on sphenotic, and relatively short pelvic fin suggest that it belongs in the genus Parateleopus Smith & Radcliffe 1912. Comments on its generic status and comparisons with all genera of the family Ateleopodidae are provided. The species is distinguished from Parateleopus microstomus, the sole congener, by 8–10 dorsal-fin rays as compared with three rays in P. microstomus.